Cultura e memória: a festa de Nossa Senhora do Rosário na cidade de Silvianópolis MG - Domingues, Andréa Silva (2007)
The research has as objective to study the customs, the performance, the arts of living and making, constituted in the daily one of the urban and agricultural space; from the values, trajectories of life and social fights of the historical agents who participate of the feast; I understand culture as integrant part of a field of changes and social disputes and politics; surrounded of interests and claims. The study it is developed through Verbal History reflecting on the ways to live of the participants of the feast, in the attempt to understand these experiences, values, daily and customs that will assist in the reflection in the way to think the collective one. Searching all the moment to perceive these experiences and processes related to feast, observing that history, for more distant than either, has for objective to provoke reflections on the current world